KNOWLEDGE OF MODIFIABLE RISK FACTORS OF CARDIOVASCULAR DISEASES AMONG PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Zuhaid, Muhammad; Kazmi, Sumera; Farooq, Umer; Khan, Ismail Alam; Aziz, Tania; Aziz, Sana; Rahim, Mahmood (Journal of Ayub Medical College Abbottabad, 2014)
Background: Cardiovascular disease is a major cause of mortality and morbidity in Pakistan. Knowledge regarding any disease is an important pre-requisite for implementation of preventive and control measures. This study aimed to evaluate the knowledge of modifiable risk factors of cardiovascular diseases in acute myocardial infarction (MI) patients admitted to Ayub Teaching Hospital, Abbottabad, Pakistan. Methods: It was a hospital based cross sectional descriptive study carried out in cardiology unit of Ayub Teaching Hospital, on 150 patients with first attack of acute MI. knowledge of four modifiable risk factors; fatty food consumption, smoking, physical activities and obesity , was assessed. Results: Among 150 subjects, 103 (68.7%) were males while 47 (31.3%) were females. Forty three (28.7%) of the patients were having good level of knowledge. Male gender and educational status were associated with good level of knowledge. Conclusion: There is a lack of good level of knowledge among patients admitted with acute MI. Implementing aggressive educational strategies is of utmost importance in Pakistani population for preventing the rising prevalence of this disease to combat the burden of MI. Keywords: Knowledge, modifiable risk factors, MI, Myocardial Infarction, Pakistan